Dysregulated hepatic lipid metabolism and gut microbiota associated with early-stage NAFLD in ASPP2-deficiency mice - Xie, Fang; Xu, Hang-fei; Zhang, Jing; Liu, Xiao-ni; Kou, Bu-xin; Cai, Meng-yin; Wu, Jing; Dong, Jin-ling; Meng, Qing-hua; Wang, Yi; Chen, Dexi; Zhang, Yang (Frontiers in Immunology, 2022)
Growing evidence indicates that lipid metabolism disorders and gut microbiota dysbiosis were related to the progression of non-alcoholic fatty liver disease (NAFLD). Apoptosis-stimulating p53 protein 2 (ASPP2) has been reported to protect against hepatocyte injury by regulating the lipid metabolism, but the mechanisms remain largely unknown. In this study, we investigate the effect of ASPP2 deficiency on NAFLD, lipid metabolism and gut microbiota using ASPP2 globally heterozygous knockout (ASPP2+/-) mice. ASPP2+/- Balb/c mice were fed with methionine and choline deficient diet for 3, 10 and 40 day to induce an early and later-stage of NAFLD, respectively. Fresh fecal samples were collected and followed by 16S rRNA sequencing. HPLC-MRM relative quantification analysis was used to identify changes in hepatic lipid profiles. The expression level of innate immunity-, lipid metabolism- and intestinal permeability-related genes were determined. A spearman’s rank correlation analysis was performed to identify possible correlation between hepatic medium and long-chain fatty acid and gut microbiota in ASPP2-deficiency mice. Compared with the WT control, ASPP2-deficiency mice developed moderate steatosis at day 10 and severe steatosis at day 40. The levels of hepatic long chain omega-3 fatty acid, eicosapentaenoic (EPA, 20:5 n-3) and docosahexaenoic (DHA, 22:6 n-3), were decreased at day 10 and increased at day 40 in ASPP+/- mice. Fecal microbiota analysis showed significantly increased alpha and beta diversity, as well as the composition of gut microbiota at the phylum, class, order, family, genus, species levels in ASPP2+/- mice. Moreover, ASPP-deficiency mice exhibited impaired intestinal barrier function, reduced expression of genes associated with chemical barrier (REG3B, REG3G, Lysozyme and IAP), and increased expression of innate immune components (TLR4 and TLR2). Furthermore, correlation analysis between gut microbiota and fatty acids revealed that EPA was significantly negatively correlated with Bifidobacterium family. Our findings suggested that ASPP2-deficiency promotes the progression of NAFLD, alterations in fatty acid metabolism and gut microbiota dysbiosis. The long chain fatty acid EPA was significantly negatively correlated with Bifidobacterial abundance, which is a specific feature of NAFLD in ASPP2-deficiency mice. Totally, the results provide evidence for a mechanism of ASPP2 on dysregulation of fatty acid metabolism and gut microbiota dysbiosis.